Ultraslow conformational dynamics and catch bond formation of a bacterial adhesin revealed by a single-domain variant of FimH - Pearl Magala; Lisa M. Tuttle; Gianluca Interlandi; Laura A. Carlucci; Molly Y. Mollica; Maria K. Janowska; Wendy E. Thomas; Evgeni V. Sokurenko; Rachel E. Klevit (Proceedings of the National Academy of Sciences, 2026)
Bacterial fimbrial adhesins such as FimH are critical for host colonization and persistence under the mechanical forces encountered at sites of infection such as the urinary tract. The molecular mechanisms by which FimH, a key virulence factor of uropathogenic Escherichia coli , regulates its binding to host cell surface mannose moieties through conformational switching remain incompletely understood. FimH operates across a range of conformations that includes low- (LAS), intermediate-, and high-affinity (HAS) states and forms catch bonds that paradoxically strengthen under force. The allosteric pathways governing these transitions remain poorly defined due to experimental limitations that restrict understanding of key dynamic phenomena that underlie ligand-triggered conformational shifts and force-induced long-lived interactions. Such understanding is central to drug discovery efforts to target bacterial adhesion. Here, we present a model system that fully recapitulates the conformational repertoire of FimH in the absence of its pilin domain. Our findings demonstrate that a single mutation in the lectin domain stabilizes the LAS while allowing for ligand-binding-induced transition to a HAS-like conformation and catch bond formation, mirroring the behavior of the native FimH adhesin. We propose a dynamic allosteric mechanism that involves ultraslow, low-frequency dynamics for the ability of FimH to sustain long-lived interactions with mannose, under both static and force conditions.